A new species of Eimeria Schneider, 1875 (Apicomplexa: Eimeriidae) from Alectoris barbara (Aves: Phasianidae) from the Canary Islands (Spain) - Fernández-Alvarez, A; Modry, D; Foronda, P (Parasitology research, 2016)
The present study was conducted with the objective of identifying the species of Eimeria present in a cynegetic farm. A new coccidian (Apicomplexa: Eimeriidae) species is described from Barbary partridge, Alectoris barbara, from the Canary Islands. Experimental infections were carried out in order to determine the prepatent period, sporulation time, site of infection, and morphology of endogenous stages. One species is described as new. Eimeria barbarae n. sp. has ellipsoidal oocysts, 20.0 × 14.4 (16-23 × 13-16) μm, with a shape-index (SI) of 1.39. Sporocysts are almond-shaped, 9.0 × 5.4 (6.5-11 × 4.5-6) μm, SI = 1.56. The endogenous development takes place along the intestine. The present study showed that E. barbarae causes severe pathologies in A. barbara chickens, with impact on their health condition. Control strategies needs to be implemented to reduce the loss due to coccidiosis at studied farm.
Keywords: Sporozoites; kur domácí; Animals; Španělsko; oocysty; Poultry Diseases; Oocysts; Eimeria; zvířata; feces; sporozoiti; Feces; nemoci drůbeže; Spain; Chickens; kokcidióza; Coccidiosis